Identification and proposed strategy for minimizing defects using the lean six sigma method in the pallet production process - Kulsum Kulsum; Reza Fawzi Rahman; Evi Febianti (Faculty of Engineering, Universitas Sultan Ageng Tirtayasa, 2021)
Judul: Identifikasi dan usulan strategi minimasi produk cacat menggunakan metode lean six sigma pada proses produksi pallet Title: Identification and proposed strategy for minimizing defects using the lean six sigma method in the pallet production processPerusahaan yang menjadi objek penelitian bergerak dalam bidang pembuatan pallet dan dunnage. Dalam proses produksi pallet masih banyak terjadi pemborosan dan produk cacat. Tujuan utama dari penelitian ini adalah untuk mengidentifikasi dan mengusulkan strategi untuk meminimalkan produk cacat melalui tahap pencarian critical to quality (CTQ) yang terjadi. Penelitian ini menggunakan metode lean six sigma sebagai solusi untuk mengatasi permasalahan tersebut. Pada pallet ditemukan 3 produk CTQ yaitu retak, pecah, dan berjamur. Berdasarkan penyebaran kuesioner waste assessment model (WAM), diketahui waste yang paling dominan adalah waste defect. Sehingga usulan perbaikan adalah membuat standar operasional prosedur (SOP), membuat checklist untuk penggantian dan perawatan mesin, melakukan pelatihan operator, pengadaan peralatan keselamatan, dan membuat tempat khusus untuk penyimpanan bahan baku. The object of this research is a company engaged in the manufacture of pallets and dunnage. In the pallet production process, there is still a lot of waste and defective products. The primary purpose of this study is to identify and propose strategies to minimize defective products through the critical to quality (CTQ) search stage that occurs. This study uses the lean six sigma method as a solution to overcome these problems. On the pallet found 3 CTQ products, namely cracked, broken, and moldy. Based on the waste assessment model (WAM) questionnaire distribution, it is known that the most dominant waste is defect waste. The improvement proposals obtained are making standard operating procedures (SOP), making checklists for machine replacement and maintenance, conducting operator training, procuring safety equipment, and creating a special place for raw material storage.